2006
DOI: 10.1086/503568
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Rule-Based Algorithm with a Phenotype-Based Algorithm for the Interpretation of HIV Genotypes in Guiding Salvage Regimens in HIV-Infected Patients by a Randomized Clinical Trial: The Mutations and Salvage Study

Abstract: Both the virtual phenotype and rule-based interpretation methods of HIV genotyping can guide the selection of effective antiretroviral drugs for a salvage regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
(21 reference statements)
2
6
0
Order By: Relevance
“…This was a retrospective study. The patients had participated in the Mutations and Salvage (MUSA) study [Gianotti et al, 2006], in which only selected centers participated in sample collection. Human PBMCs from HIV1-positive individuals were cryopreserved.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a retrospective study. The patients had participated in the Mutations and Salvage (MUSA) study [Gianotti et al, 2006], in which only selected centers participated in sample collection. Human PBMCs from HIV1-positive individuals were cryopreserved.…”
Section: Samplesmentioning
confidence: 99%
“…In order to evaluate whether different therapeutic histories were associated with different mRNA transporter expression levels, samples were divided into three groups on the basis of their treatment history [Gianotti et al, 2006].…”
Section: Expression Of Abc-transporters and Therapeutic Historymentioning
confidence: 99%
“…Paired plasma and whole blood samples were collected from the first 80 patients participating in the Italian multicentric Mutations and Salvage (MuSa) Study [Gianotti et al, 2006]. The MuSa study was a randomized clinical trial which enrolled HIV-infected patients during virological failure at their first or second HAART regimen; the study compared a rule-based and a phenotypic-based algorithm for the interpretation of HIV genotypes to guide salvage regimens.…”
Section: Patientsmentioning
confidence: 99%
“…Most studies have found a therapeutic advantage in terms of likelihood of viral suppression and mean virologic RNA reduction for resistance-test-guided treatments when compared to treatments based only on clinical judgment (DeGruttola et al, 2000;Durant et al, 1999;Gianotti et al, 2006;Ormaasen et al, 2004;Tural et al, 2002). Consequently, most international guidelines recommend resistance to assist the selection of therapeutic regimens following pharmacologic viral failure (DDHS, 2006Vandamme et al, 2004).…”
Section: Clinical Value Of Hiv Drug Resistance Testingmentioning
confidence: 99%
“…Common limitations for all resistance tests are inability to detect virus archived in viral reservoirs, insensitivity to viral quasispecies that represent less than 20% of the total viral mixture, and the requirement of a minimum viral load (500-1000 plasma HIV RNA copies/milliliters) for the test to be performed. Current methods appear to have similar performance at detecting antiretroviral resistance (Ferrer et al, 2003;Gianotti et al, 2006;Mazzotta et al, 2003;Saracino et al, 2004), but GART is more sensitive for minority populations than PART. Consequently, GART can detect sentinel mutations (e.g., M184V) before changes in phenotypic resistance become evident.…”
Section: Clinical Value Of Hiv Drug Resistance Testingmentioning
confidence: 99%